An assessment of inequality estimates for the case of South Africa - Muna Shifa; Rejoice Mabhena; Vimal Ranchhod; Murray V. Leibbrandt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
A substantial amount of research has been conducted examining inequality in South Africa using multiple data sources. We provide an overview of this research in this paper. Furthermore, we use nationally representative survey data to estimate income and consumption inequality in South Africa between 1993 and 2017, and we discuss the comparability of income and consumption measures across surveys. We compare our estimates of inequality to those in the World Income Inequality Database (WIID), which provides adjusted inequality estimates to ensure consistency across time and countries. Despite these adjustments, there are some large fluctuations in income inequality estimates from the WIID,which can be partly attributed to data comparability problems. The overall trend in post-apartheid South Africa indicates an increase in income and wealth inequality. However, estimates of inequality levels over time are influenced in part by methodological changes implemented across multiple surveys over time, making definitive conclusions about inequality levels and trends difficult.
Keywords: D21; C83; 330; income distribution; inequality; surveys; South Africa